IPTEKS ANGGARAN KAS UNTUK IBU – IBU PKK DI DESA KAUDITAN I KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Karamoy, Herman; Wokas, Heince Rudy Nicky (Universitas Sam Ratulangi, 2019)
Performance-based budgeting is very important for firm management in case to estimte the ending financial statement. Also performance-based budgeting is very important to control the inflows and outflows of cash. Kauditan village is one of developed region in North Sulawesi but most of household in that area still have less understanding about budgeting especially cash budget. The applied science about cash budgeting is effective for those household in Kauditan village.